RT-SCNNs: Real-time spiking convolutional neural networks for a novel hand gesture recognition using time-domain mm-wave radar data - Shaaban, Ahmed; Strobel, Maximilian; Furtner, Wolfgang; Weigel, Robert; Lurz, Fabian (International Journal of Microwave and Wireless Technologies, 2024)
This study introduces a novel approach to radar-based hand gesture recognition (HGR), addressing the challenges of energy efficiency and reliability by employing real-time gesture recognition at the frame level. Our solution bypasses the computationally expensive preprocessing steps, such as 2D fast Fourier transforms (FFTs), traditionally employed for range-Doppler information generation. Instead, we capitalize on time-domain radar data and harness the energy-efficient capabilities of spiking neural networks (SNNs) models, recognized for their sparsity and spikes-based communication, thus optimizing the overall energy efficiency of our proposed solution. Experimental results affirm the effectiveness of our approach, showcasing significant classification accuracy on the test dataset, with peak performance achieving a mean accuracy of 99.75%. To further validate the reliability of our solution, individuals who have not participated in the dataset collection conduct real-time live testing, demonstrating the consistency of our theoretical findings. Real-time inference reveals a substantial degree of spikes sparsity, ranging from 75% to 97%, depending on the presence or absence of a performed gesture. By eliminating the computational burden of preprocessing steps and leveraging the power of (SNNs), our solution presents a promising alternative that enhances the performance and usability of radar-based (HGR) systems.
CRIS-Team Scopus Importer:2025-02-04
Keywords: FMCW radar; radar gesture recognition; radar signal processing; spiking neural networks